The usage of Arabic language learning strategies (ALLS) among Sultan Ismail Petra International Islamic College (KIAS) - Kamarul Shukri, Mat Teh; Linamalini, Mat Nafi (2019)
Various studies show that the usage of the Arabic language learning strategies among the students in Malaysia is at a low and average level. There are several factors that contribute to the usage of Arabic language learning strategies. Among them are the Arabic language achievement, language motivation, gender, duration of study and parents’ educational level. Thus, this study aims to explore the ALLS usage by students when learning Arabic language and studying the factors which contribute to the ALLS usage. This study involved 100 respondents from International Islamic College Sultan Ismail Petra (KIAS). This quantitative survey study used questionnaires of Learning Language Strategy SILL version 7.0 as a primary research tool to collect data. The study findings show that Metaphysics strategy is a strategy which is most frequently used by students, while cognitive strategy is the strategy which is the least used by students. It is also indicating that students used all strategies at an average level.